A Review in Research Progress Concerning m6A Methylation and Immunoregulation - Zhang, Caiyan; Fu, Jinrong; Zhou, Yufeng (Frontiers in Immunology, 2019)
Over 100 types of cellular RNA modifications have been identified in both coding and a variety of noncoding RNAs. N6-methyladenosine (m6A) is the most prevalent and abundant post-transcriptional RNA modification on eukaryote mRNA, and its biological functions are mediated by special binding proteins (i.e. methyltransferases, demethylases, and effectors) that recognize this modification. The presence of m6A on transcripts contributes to diverse fundamental cellular functions, such as pre-mRNA splicing, nuclear transport, stability, translation, and microRNA biogenesis, implying an association with numerous human diseases. This review principally summarizes recent progress in the study of m6A methylation mechanisms and relevant roles they play in immunoregulation.